100k views
1 vote
Simplify by expressing fractional exponents instead of radicals

Simplify by expressing fractional exponents instead of radicals-example-1
User IElectric
by
5.2k points

2 Answers

6 votes

Answer:

ab = (ab)^(1/2)

Explanation:

Odyssey ware

User Hharnisc
by
5.9k points
7 votes

Answer:


a^{(1)/(2)}b^{(1)/(2)}

Explanation:

Given:

The expression in radical form is given as:


√(ab)

We need to express this in fractional exponent form.

We know that,


\sqrt a=a^{(1)/(2)}

Also,
√(ab)=\sqrt a* \sqrt b

Now, clubbing both the properties of square root function, we can rewrite the given expression as:


√(ab)=\sqrt a * \sqrt b\\\\√(ab)=a^{(1)/(2)}* b^{(1)/(2)}\\\\\therefore √(ab)=a^{(1)/(2)}b^{(1)/(2)}

So, the given expression in fractional exponents form is
a^{(1)/(2)}b^{(1)/(2)}.

User Eric Galluzzo
by
6.3k points